Strategi Promosi dan Pengembangan 5 Objek Wisata Unggulan Desa Telagah Kabupaten Langkat - Amelia Putri; Dita Ayu Susmita; Aninda Muliani (Reslaj : Religion Education Social Laa Roiba Journal, 2023)
Due to the COVID-19 pandemic, in December 2021 the number of foreign tourists from North Sumatra reached 0 visits, this is directly proportional to the lack of tourists visiting Telagah Village both locally and non-locally, therefore a strategy is needed to increase the number of tourist visits. This study aims to formulate a strategy for the promotion and development of 5 leading tourism objects in Telagah village, namely the Barbar Sari/ Lau Kulap Tourism Object, Rumah Ladang Tourism Object, Pamah View Tourism Object, Kolam Karona Sakti Tourism Object, and Wisata Tidur Sawah Tourism Object. This research uses a qualitative descriptive approach, which consists of a qualitative analysis in the form of a study of literature related to observations using a check list sheet, interviews/discussions focused on the development efforts made by the village community towards Telagah Village tours. By combining analysis of promotion and development strategies through demographic analysis, tourist perceptions of attractions, amenities, accessibility, image, and price. The results of the study reveal that an effective promotion strategy that uses market segmentation, development and development of the four aspects above (attractions, convenience, accessibility, image) at affordable prices can improve the quality of facilities and infrastructure around tourist objects which in turn can increase the number of tourists. Key words : Innovation, Management, Promotion, Strategy, Village Tourism.